Dari Tionghoa ke Tjina: Telaah Sejarah terhadap Demonisasi Etnis Tionghoa di Indonesia [From Tionghoa to China: A Historical Review of the Demonization of Chinese Ethnicity in Indonesia] - Michael J. Kristiono (Universitas Pelita Harapan, 2018)
This paper attempts to investigate the reasons behind the negative sentiments directed towards Chinese Indonesians from an International Relations (IR) perspective. By tracing back the treatment of the New Order government towards ethnic Chinese, it was found that such demonization initially happened due to two politically motivated reasons. Firstly, as part of de-Soekarnoization done by the New Order, the Chinese were outcast because Chinese identity does not conform to the “Indonesian identity”, which was in essence, the Javanese identity. Secondly, the condition reflected the change in Indonesian foreign policy which drifted apart from People’s Republic of China (PRC) as the latter was suspected to be involved in September 30 Movement. Then, I argue that due to those reasons, coupled by systematic maltreatment from the New Order Government, Chinese Indonesians were constructed as the “others”, that is, as non-Indonesians. Such construct has been deeply embedded such that reconciliation attempts done by the Reformation Era government were not sufficient enough to stop ethnic discrimination towards Chinese Indonesians from happening even until the present.